Hauntologies of Domestic Space in Contemporary Women's Writing, 1985-2015: Alice Munro, Lorrie Moore, and Anne Enright. - Houston, Dearbhaile Sophie (Trinity College Dublin. School of English. Discipline of English, 2022)
This dissertation utilises a hauntological understanding of domestic space in order to examine spectral presences in the fiction of three contemporary women writers, Alice Munro, Lorrie Moore, and Anne Enright, focusing on work published between 1985 and 2015. Taking into account theoretical, cultural, and literary responses to domestic space and its meanings, the study establishes a way of analysing haunted domestic spaces in contemporary realist fiction authored by women beyond established modes. The study is organised into four sections, beginning with a theoretical chapter which outlines ?thinking hauntologically? about domestic space as a cultural and literary entity. This is followed by three chapters which focus on Munro, Moore, and Enright?s respective fiction (incorporating novels and short stories), through a close reading of the particular spectral presences found within the domestic spaces in each author?s work. In this study, I argue that hauntology?s focus on the temporal disruption heralded by the arrival of the spectre, as established in Jacques Derrida?s Specters of Marx and further developed in literary and cultural studies, can be applied to the study of domestic space. This is established by analysing the pervasiveness of the spectre in spatial theories from the Gothic mode to psychoanalysis, and critical and feminist theory. As such, the haunted house is a wide-ranging concept that powerfully articulates long-standing domestic ambivalences and dissatisfactions with the domestic space in contemporary women?s writing beyond generic conventions. Each chapter begins by offering an overview of cultural attitudes and legal frameworks pertaining to women?s economic labour, legal protections within the home, and the organisation of the family in Canada, the United States, and Ireland, producing a snapshot of domestic discourses in the public sphere specific to the cultural context of each author. This is followed by close readings of spatial descriptions of domestic space and its associated labour and relationships in the selected fiction. These readings are structured by theme: space and place, domestic architecture, and domestic objects. In a selection of Munro?s short stories published in the latter half of her career, from 1986 to 2012, the spectres that haunt the domestic space relate to memory. Associated with instances of trauma inherited within family structures or emerging from murder or accidental death, such spectres are a trace present within the Canadian domestic space as a specifically mnemonic site. This chapter considers Munro?s treatment of domestic space and themes as deconstructive of normative visions of spatial organisation and the home in women?s writing. Spectres of failure mark the domestic spaces in Moore?s short stories and novels published from 1985 to 2013. These spectres manifest in response to the post-war image of the American domestic space as one of economic productivity and sexual reproduction and the increasing precarity of the contemporary home. This chapter offers an analysis of domestic space in Moore?s oeuvre as a means of addressing the gaps in scholarship on her fiction, arguing for an understanding of Moore as a writer who addresses wider issues, from post-war gender politics to post-9/11 political rhetoric, specifically through the motif of haunted domestic space. In Enright?s novels published from 1995 to 2015, spectres of silence haunt the Irish domestic space. This chapter positions Enright?s hauntology of domestic space as a specifically ethical response to the elision of post-independence Ireland?s history of abuses towards women and children, which emerge as a spectral presence in the prosperous settings of modern and Celtic Tiger domestic spaces. The study concludes with a reflection on Munro, Moore, and Enright?s respective hauntologies of domestic space and how they suggest ways for ?living with? spectres in the contemporary moment. This dissertation opens up avenues for further research on domestic spaces in contemporary women?s writing, particularly in fiction that engages with images of haunted space outside of the Gothic genre. Through its use of hauntology and its focus on material elements of space, the study sheds new light on the domestic space as an important category of analysis in literary studies, and broadens its scope of understanding beyond codified values of the private sphere.
APPROVED
Keywords: women's writing; contemporary fiction; domestic space; hauntology; Anne Enright; Alice Munro; Lorrie Moore